Odpowiedzi

2010-02-18T16:51:28+01:00
A)4x-3=3x+5
4x-3x-3-5=0
x-8=0
x=8

b)5x+2=7-3x
5x+3x=7-2
8x=5
x=5/8

c)3(x-1)=0
3x-3=0
3x=3
x=1

d)-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30
x=-5

e)-7(x-2)=3x-1
-7x+14=3x+1
-7x-3x=1-14
-10x=-13
x=1,3

f)4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10
x=-5

pozdrawiam:)
2010-02-18T16:52:21+01:00
A)4x-3=3x+5
4x-3x=5+3
x=8
b)5x+2=7-3x
5x+3x=7-2
8x=5/:8
x=5/8
c)3(x-1)=0
3x-3=0
3x=3
x=3
d)-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30/:(-6)
x=-5
e)-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15/:(-10)
x=3/2
f)4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10/(-2)
x=-5
2010-02-18T16:55:50+01:00
*4x-3=3x+5
4x-3x=3+5
x=8
*5x+2=7-3x
5x+3x=7-2
8x=5
*3(x-1)=0
3x -3=0
3x=0+3/3
x=1
*-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30/(-6)
x=(-5)
*-7(x-2)=3x-1
-7x+14=3x-1
-7x3x=-14-1
-4x=-15/(-4)
x=15/4
*4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=4+6
-2x=10/(-2)
x=(-5)